Alternative approach for reproducing the in-plane behaviour of rubble stone walls - Tarque, Nicola (2017)
Stone masonry is one of the oldest construction types due to the natural and free availability of stones and the relatively easy construction. Since stone masonry is brittle, it is also very vulnerable and in the case of earthquakes damage, collapses and causalities are very likely to occur, as it has been seen during the last Italian earthquake in Amatrice in 2016. In the recent years, some researchers have performed experimental tests to improve the knowledge of the behaviour of stone masonry. Concurrently, there is the need to reproduce the seismic behaviour of these structures by numerical approaches, also in consideration of the high cost of experimental tests. In this work, an alternative simplified procedure to numerically reproduce the diagonal compression and shear compression tests on a rubble stone masonry is proposed within the finite element method. The proposed procedure represents the stone units as rigid bodies and the mortar as a plastic material with compression and tension inelastic behaviour calibrated based on parametric studies. The validation of the proposed model was verified by comparison with experimental data. The advantage of this simplified methodology is the use of a limited number of degrees of freedom which allows the reduction of the computational time, which leaves the possibility to carry out parametric studies that consider different wall configurations.